2019
DOI: 10.3390/foods8110557
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Non-Polar and Polar Metabolites in 14 Soybeans Using Spectroscopy and Chromatography Tools

Abstract: There has been significant interest in soybean oil, fatty acid, and sugar composition to develop new value-added soybean products. Thus, compositional analysis is critical for developing value-added soybeans. In the present study, we showed simple screening tools (near infrared spectroscopy (NIR) and high-performance thin layer chromatography (HPTLC)) coupled with multivariate analysis for the sample classification of 14 soybeans as a proof-of-concept. We further determined major non-polar and polar metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Soluble sugars were extracted by using modified extraction methods previously reported. 14,15 The sample preparation optimization was done in three steps. Initially, extractions with lima beans were carried out in triplicates for four different time periods (15,30,60, and 90 min) using 25 ± 0.1 mg of ground sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble sugars were extracted by using modified extraction methods previously reported. 14,15 The sample preparation optimization was done in three steps. Initially, extractions with lima beans were carried out in triplicates for four different time periods (15,30,60, and 90 min) using 25 ± 0.1 mg of ground sample.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…14,15 The sample preparation optimization was done in three steps. Initially, extractions with lima beans were carried out in triplicates for four different time periods (15,30,60, and 90 min) using 25 ± 0.1 mg of ground sample. Extraction was carried out with 5 mL of water in a disposable 15 mL centrifuge tube.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Similarly, the presence of epicatechin and sugars have also been reported previously by Hyeon et al and Song et al [ 29 , 30 ]. We also reported in our earlier publication the presence of sugars in soybean by ion chromatography and fatty acids after derivatization using GC-MS analysis with targeted analysis [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the free amino acids and organic acids varied between the varieties [ 20 ]. In a recent study, we reported the compositional analysis of fatty acids and soluble sugars in wild and cultivated 14 soybeans genotypes using targeted analysis [ 21 ]. We observed differences in total oil content in wild soybeans (~9%) versus cultivated soybeans (16–22%).…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil contained the highest percentage of oleic acid (89%) while virgin coconut oil contained 7.6%. Kotha et al [19] showed that the higher concentration of oleic acid in oils can decrease low-density lipoprotein (LDL)-cholesterol without decreasing the high-density lipoproteins (HDL) cholesterol.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%